Character Formation of Students in Elementary Schools Through Citizenship Education - Harahap, Lutfia Nadiroha (International Journal of Students Education, 2024)
Developing the character of elementary school students through civic education is a strategic initiative to produce a young generation with integrity, responsibility, and awareness. high social. The research method used in this article is use method qualitative. Then for the method used that is with method studies literature review. Civic education noto only aims to instill an understanding of the rights and responsibilities of citizenship, but also teaches moral and ethical values that are important in everyday life. Through an interactive value-based curriculum approach, students are encouraged to understand the importance of tolerance, mutual cooperation, integrity, and love of the homeland. The current era of globalization is marked by sophisticated technology, various easily accessible information, and a rapidly growing population. This education can be carried out through various learning methods such as discussions, simulations, and role plays that can effectively instill positive values in students. Therefore, civic education in elementary schools plays an important role in building the character of students who are prepared to become good and responsible citizens in the future. The implementation of character education in elementary schools can be included in the learning process such as several subjects, one of which is the subject of Civic Education.